CP-151 Assessment of an experimental call centre dedicated to drug information for outpatients. (25th February 2017) - Rhodes, P; Ferreira, V; Agullo, M; Piriou, G; Varin, R; Collomp, R; Boronad, C
Abstract : Background: A national innovative telephone drug information service, called MiS, was implemented in April 2016 to improve diffusion of information about drugs and health products. MiS consists of four networked drug information centres (DIC) which provide free, reliable and objective information to healthcare providers and patients. All telephone queries are processed by experienced and trained pharmacists. Purpose: The aim of the study was to assess the perceived clinical impact of pharmacists' interventions and users' satisfaction of the unique MiS DIC dedicated to outpatients. Material and methods: Three surveys were conducted from the analysis of the first 200 queries:(1) extraction from MiS question/response database to highlight the main themes;(2) peer review of each intervention to highlight perceived clinical and/or economic impacts, using the Hatoum scale; and (3) a satisfaction survey was conducted by telephone interview with patients. Results: Of 200 queries, 89% concerned approved drugs, 9% other health products (eg, dietary supplements) and 2% medical devices. The main patient concerns were adverse effects (23%), drug interactions (20%) and indications/contraindications (14%), mainly regarding cardiovascular (20%), nervous system (16%) and anti-infective (10%) treatments. MiS interventions were judged to have a clinical impact in 86% of cases by optimising drug therapy (68%) and preventing potential adverse events (32%), and an economic impact in 25%. Drug therapy optimisation consists of improving patient compliance (28%), seamless care (18%) and proper use of drugs (15%) whereas iatrogenic prevention consists of avoiding drug misuse (12%). Globally, the perceived impact of MiS was deemed 'significant' in 53%, 'very significant' in 24% and 'vital' in 4%. In addition, the satisfaction survey revealed that most patients (>80% of 149 respondents) were very satisfied with the relevance and usefulness of the information delivered. Conclusion: Despite self-assessment bias, our results highlight the fact that most MiS interventions had a perceived clinical impact, particularly in improving patient compliance and proper use of drugs, guaranteeing drug effectiveness. Associated with a high level of user satisfaction, MiS represents a real need for outpatients who search for reliable drug information and the accessibility of this service must be sustained and expanded. No conflict of interest